Effects of a wholegrain-rich diet on markers of colonic fermentation and bowel function and their associations with the gut microbiome: a randomised controlled cross-over trial - Procházková, Nicola; Venlet, Naomi; Hansen, Mathias L.; Lieberoth, Christian B.; Dragsted, Lars Ove; Bahl, Martin I.; Licht, Tine Rask; Kleerebezem, Michiel; Lauritzen, Lotte; Roager, Henrik M. (Frontiers in Nutrition, 2023)
Background Diets rich in whole grains are associated with health benefits. Yet, it remains unclear whether the benefits are mediated by changes in gut function and fermentation. Objective We explored the effects of whole-grain vs. refined-grain diets on markers of colonic fermentation and bowel function, as well as their associations with the gut microbiome. Methods Fifty overweight individuals with increased metabolic risk and a high habitual intake of whole grains (~69 g/day) completed a randomised cross-over trial with two 8-week dietary intervention periods comprising a whole-grain diet (≥75 g/day) and a refined-grain diet (<10 g/day), separated by a washout period of ≥6 weeks. A range of markers of colonic fermentation and bowel function were assessed before and after each intervention. Results The whole-grain diet increased the levels of faecal butyrate (p = 0.015) and caproate (p = 0.013) compared to the refined-grain diet. No changes in other faecal SCFA, BCFA or urinary levels of microbial-derived proteolytic markers between the two interventions were observed. Similarly, faecal pH remained unchanged. Faecal pH did however increase (p = 0.030) after the refined-grain diet compared to the baseline. Stool frequency was lower at the end of the refined-grain period compared to the end of the whole-grain diet (p = 0.001). No difference in faecal water content was observed between the intervention periods, however, faecal water content increased following the whole-grain period compared to the baseline (p = 0.007). Dry stool energy density was unaffected by the dietary interventions. Nevertheless, it explained 4.7% of the gut microbiome variation at the end of the refined-grain diet, while faecal pH and colonic transit time explained 4.3 and 5%, respectively. Several butyrate-producers (e.g., Faecalibacterium, Roseburia, Butyriciococcus) were inversely associated with colonic transit time and/or faecal pH, while the mucin-degraders Akkermansia and Ruminococcaceae showed the opposite association. Conclusion Compared with the refined-grain diet, the whole-grain diet increased faecal butyrate and caproate concentrations as well as stool frequency, emphasising that differences between whole and refined grains affect both colonic fermentation and bowel habits.